Analysis of BABA (β-aminobutyric acid)-induced female sterility in Arabidopsis flowers - Kocsis, Marianna; Jakab, Gábor (Acta Biologica Szegediensis, 2008)
The beta-aminobutyric acid (BABA) induces resistance in plants against a wide range of pathogen, affecting callose production and deposition in Arabidopsis. Repeated treatment with BABA, however effects the pollination of the ovules resulting female sterility. The main reasons of this phenomenon out of the structural changes in the treated Arabidopsis plants can be the interrupted pollen tubes and the callose deposition at the ovule micropyle in flowers and buds.